Aspects of the Manifestations of Scientific Exchange between Algeria and the Hijaz during the 12th Century AH / 18th Century CE - Griza, Rabia; Bichi, Rahima (The Algerian Historical Journal, 2026)
This research paper aims to shed light on the activities of Algerian scholars and students in the Hijaz, a region unmatched in human history for the millions of people who have made pilgrimages to it in every generation. This paper also seeks to address certain aspects of scientific communication between Algeria and the Hijaz. Algerian pilgrimage journeys were motivated by both the pursuit of knowledge and the fulfillment of the Hajj obligation. Thus, scholars traveled between various countries in search of learning and to meet with other scholars. It was natural for the performance of the pilgrimage rites to be accompanied by the pursuit of knowledge, where this scientific interaction and communication between Algerians and the scholars in the Hijaz became evident. Some of these scholars even settled near the Holy Kaaba and the Prophet's Mosque, both receiving and imparting knowledge, resulting in the compilation of scholarly works and the granting of academic certifications (ijāzāt).